Maqasid ibadah haji dalam perspektif sunnah: Kajian terhadap kefahaman dan amalan jemaah haji Malaysia / Rizalman Muhammad - Rizalman , Muhammad (2016)
This research analyzes the hadith texts of the hajj (pilgrimage) to identify the hajj maqasid in the Sunnah perspective. Altogether, 1,947 hadith texts relating to hajj in the al-Sunan al-Sittah has been screened and takhrij analysis has been performed. It is found that there are 105 hadith texts that are related to the practice of hajj of the Prophet and maqasid pilgrimage. 98 of them are authentic hadith texts, and 7 are hasan hadith texts. Of these, 49 texts are focusing on various aspects of hajj as done by the Prophet and 56 texts focusing on the maqasid pilgrimage. The study found that many maqasid and legal principles should be adopted in performing hajj. In this research, surveys and observations have been conducted to compare between Malaysian pilgrims practice of hajj and the way that has been performed by the Prophet. Based on descriptive questionnaire survey involving 379 respondents, it has been shown that the understanding of Malaysian pilgrims to the purposes of pilgrimage in the Sunnah perspective is just at a moderate level. The inference test, t-test and Anova studies indicate that the practice of Malaysian pilgrims on the Sunnah is also at very moderate level. Education and frequency of performing hajj factors do not have any influence on the variables used to measure the level of respondents. While gender and education level, only slightly affect the level of hajj practice by the respondents. Experience attending the hajj courses, is not significant to the understanding and practice of the maqasid hajj according to the Sunnah of the Malaysian pilgrims. The pilgrims will have very good understanding of hajj and thus greatly influence their practice of hajj mostly due to their previous knowledge and good explanation by the speakers during the course. The pilgrim understanding level is not because of the module provided by the Hajj Pilgrims Fund Board itself.